Aspect ratio control of layered double hydroxide nanosheets and their application for high oxygen barrier coating in flexible food packaging - Yu, J; Buffet, J-C; O'Hare, D (American Chemical Society, 2020)
We report a method to rationally control the aspect ratio of layered double hydroxide for use as a barrier coating for food packaging films. The reconstruction of a Mg2Al-layered double oxide (LDO) in concentrated aqueous glycine solutions produces dispersions of Mg2Al-LDH nanosheets. The nanosheet thickness decreases and diameter increases with increasing reconstruction time from 16 to 96 h. We observe a limiting nanosheet aspect ratio of ca. 336 ± 170. These Mg2Al-LDH nanosheets can be dispersed in PVA to give a water-based dispersion that can be used to coat flexible polymeric films. Oxygen transmission rate (OTR) of a PET film decreases when the thickness of the dried coated layer increases, an OTR of <0.005 mL·m–2·day–1 is observed for a coating with thickness of 1175 ± 101 nm.